2017
DOI: 10.1093/ntr/ntw287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Switching to the Tobacco Heating System 2.2 Menthol, Smoking Abstinence, or Continued Cigarette Smoking on Biomarkers of Exposure: A Randomized, Controlled, Open-Label, Multicenter Study in Sequential Confinement and Ambulatory Settings (Part 1)

Abstract: IntroductionThe menthol Tobacco Heating System 2.2 (mTHS) is a newly developed candidate modified-risk tobacco product intended to reduce exposure to the harmful and potentially harmful constituents (HPHCs) of conventional cigarette (CC) smoke. This study examined the impact of switching to mTHS on biomarkers of exposure to HPHCs relative to menthol CCs (mCCs) and smoking abstinence (SA).MethodsIn this three-arm, parallel-group study, 160 Japanese adult smokers (23–65 years; smoking ≥10 mCCs per day) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
58
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 33 publications
14
58
0
2
Order By: Relevance
“…In humans, previous clinical studies showed a similar nicotine absorption profile in smokers using a single Tobacco Stick or smoking a cigarette [ 16 ] and demonstrated reductions in the levels of 15 biomarkers of exposure to HPHCs in healthy adult smokers who switched exclusively to THS 2.2 for five days in confinement or for three months in ambulatory setting relative to cigarettes. The magnitude of reductions was comparable to what was observed in adult smokers who abstained from smoking [ 16 - 18 ].…”
Section: Introductionsupporting
confidence: 78%
“…In humans, previous clinical studies showed a similar nicotine absorption profile in smokers using a single Tobacco Stick or smoking a cigarette [ 16 ] and demonstrated reductions in the levels of 15 biomarkers of exposure to HPHCs in healthy adult smokers who switched exclusively to THS 2.2 for five days in confinement or for three months in ambulatory setting relative to cigarettes. The magnitude of reductions was comparable to what was observed in adult smokers who abstained from smoking [ 16 - 18 ].…”
Section: Introductionsupporting
confidence: 78%
“…Brossard et al showed that the nicotine pharmacokinetic profile of IQOS was close to that of conventional cigarettes with similar urge-tosmoke levels [36]. The use of IQOS or glo reduced the exposure to smoke toxicants in a manner comparable to quitting tobacco use [74,75]. After switching from conventional cigarettes to HTPs (IQOS or glo), a significant reduction in the levels of biomarkers of exposure to harmful and potentially harmful constituents was observed [76][77][78].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 99%
“…The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78]. However, there have been no independent studies regarding short-term and longterm health consequences of HTP use.…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%
“…In a series of randomized clinical trials, it has been shown that biomarkers of exposure (BoExp) to HPHCs are reduced substantially in smokers switching completely to THS after only 5 days. These changes were largely maintained in an ambulatory setting, over a period of 3 months, in Japanese and American smokers who switched to THS (12,13). In addition to favorable changes in BoExp, changes in biomarkers of effect have been shown to approach those seen in smokers who quit using tobacco products altogether (13,14).…”
Section: Introductionmentioning
confidence: 95%